Atomic force microscopy - Scanning electrochemical microscopy (AFM-SECM) for nanoscale topographical and electrochemical characterization: Principles, applications and perspectives. (1st February 2020) - Shi, Xiaonan; Qing, Weihua; Marhaba, Taha; Zhang, Wen
Abstract: Atomic Force Microscopy-Scanning Electrochemical Microscopy (AFM-SECM) has evolved to be a powerful tool for simultaneous topographical-electrochemical measurements at local material surfaces with high spatial resolution. Such measurements are crucial for understanding structure-activity relationships relevant to a wide range of applications in material science, life science and chemical processes. AFM-SECM integrates classic SECM and AFM to achieve on-step acquisition of unparalleled high-spatial-resolution surface topology and nanoscale electrochemical images and holds promising potential to unveil fundamental interfacial properties or activity at nanoscale. Despite the rapid development of AFM-SECM, its unique principles, capabilities, and applications have not been sufficiently understood and utilized. The present review provides a short critical overview of the evolution of AFM-SECM, the major principles and operation modes as well as the AFM-SECM probe designs. The current applications of AFM-SECM in materials, biological and chemical sciences are critically discussed to highlight the remaining challenges of the AFM-SECM and perspectives on its further development. Graphical abstract: Image 1092281 Highlights: Combined AFM-SECM for nanoscale electrochemical characterization was reviewed. Principles and operational modes of AFM-SECM were introduced. Applications of AFM-SECM in material, biological, chemical science were discussed. Challenges and further perspectives of AFM-SECM were highlighted.